Primary Education e-Access Initiatives in India - Jain, Pooja; Babbar, Parveen; Dalal, Garima (THE PRIMARY TEACHER, 2018)
The Constitution of India guarantees free and compulsory education to all children in the age group of 6–14 years. But all children in the country are unable to get equitable access to primary education. Therefore, the Government of India has come up with numerous initiatives and programmes to create an environment so as to achieve the aim of Universalisation of Elementary Education (UEE). Some of these government initiatives encourage collaboration, cooperation, and promotion of universal, equitable, open and free access to Information and Communication Technology (ICT). The government is also keen to address the issue of openness, which provides free accessibility to resources by surfing the Internet. This paper gives an overview of various digital platforms for primary education in India, which have been initiated by the Central government for open access resources in different formats and languages. It also tries to create awareness among teachers for optimum utilisation of open access resources for primary education